2013
DOI: 10.1002/pola.26650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photovoltaic performance of donor–acceptor polymers containing benzo[1,2‐b:4,5‐b′]dithiophene with thienyl substituents

Abstract: Three alternating donor–acceptor copolymers have been synthesized by Stille coupling polymerization of 2,6‐(trimethyltin)−4,8‐bis(5‐dodecylthiophene‐2‐yl)benzo[1,2‐b:4,5‐b′]dithiophene with 1,3‐dibromo‐5‐hexylthieno[3,4‐c]pyrrole‐4,6‐dione, 4,7‐dibromo‐1,3‐benzothiadiazole, and 5,7‐dibromo‐2,3‐didodecylthieno[3,4‐b]pyrazine, respectively. The synthesized polymers were tested in bulk heterojunction solar cells as blends with the acceptor [6,6]‐phenyl‐C61‐butyric acid methyl ester (PCBM). The thienopyrroledione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…24 In order to improve the performance of PSCs, the synthetic versatility of organic chemistry is used for the development of novel materials. [32][33][34][35][36] Therefore, in this study, 4,8-bis(2-alkoxy)benzo[1,2-b:4,5-b 0 ]dithiophene (BDT) was incorporated in a benzotriazole (BTZ) and thiophene bearing polymer backbone due to its aforementioned properties. Since the first introduction of the BDT unit, it has been coupled with thieno- [3,4-b]thiophene (TT), 25,26 dithiophene-2-yl-2,1,3-benzothiadiazole (DTBT), 27 thieno [3,4-c]pyrrole-4,6-dione (TPD) 28- 30 and diketopyrrolopyrrole (DPP) to form copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…24 In order to improve the performance of PSCs, the synthetic versatility of organic chemistry is used for the development of novel materials. [32][33][34][35][36] Therefore, in this study, 4,8-bis(2-alkoxy)benzo[1,2-b:4,5-b 0 ]dithiophene (BDT) was incorporated in a benzotriazole (BTZ) and thiophene bearing polymer backbone due to its aforementioned properties. Since the first introduction of the BDT unit, it has been coupled with thieno- [3,4-b]thiophene (TT), 25,26 dithiophene-2-yl-2,1,3-benzothiadiazole (DTBT), 27 thieno [3,4-c]pyrrole-4,6-dione (TPD) 28- 30 and diketopyrrolopyrrole (DPP) to form copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…The repeating units are calculated to be 25.8 for P1, 70.3 for P2, and 23.1 for P3, respectively, Compared with P1, the P2 shows relatively high molecular weight, probably due to pendent thiophene side chain. Conjugated side‐chained polymer, compared with the semiconjugated side‐chained polymer (P2 and P3), shows similar but a little lower molecular weight.…”
Section: Resultsmentioning
confidence: 95%
“…The absorption peak wavelengths ( λ max ) in the solution and thin films and the absorption onset wavelengths ( λ onset ) are shown in Table . The basic optical properties of the polymers with the conjugated side chain and the same backboned polymer (P1, P2, and P3) are also listed in Table for comparison. The absorption spectrum of P2 and P3 become broader and show the obvious red‐shift in the solid film, which indicates more effective π–π stacking in the solid state due to pendent thiophene side chain to reduce the steric hindrance, compared with conjugated side‐chained polymer (P4) 22 with similar backbone structures.…”
Section: Resultsmentioning
confidence: 99%
“…Essentially, balanced electron/hole mobilities were obtained with proper phase separation, leading to a high fill factor. In another study of functionalized side chains with different amounts in P3HT by Janssen et al [9], the authors clearly demonstrated the possibility to tune the performances of (P3HT-based) conjugated polymer donor materials by introducing the functionalized side chains in moderate amounts, and they showed that functionalized P3AT copolymers, obtained via post-polymerization protocols from the presented esterfunctionalized P3ATs (affording alcohol and cinnamoyl moieties in the side chains), provide a considerably more stable active layer blend morphology upon prolonged thermal annealing compared to regular P3HT. In 2008, Hou and Yang reported primarily the synthesis and electronic properties of benzodithiophene (BDT)-based copolymers [23].…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, tremendous efforts have been devoted to develop novel conjugated polymers with different alternating units along the polymer backbone, and the power conversion efficiencies (PCEs) of PSCs based on these polymers have been improved from about 1 % to more than 9 % [7][8][9][10][11][12]. For example, donor-acceptor conjugated polymers with alternating electron-rich (donor) and electron-deficient (acceptor) units can achieve appropriate band gap and energy level by controlling the intramolecular charge transfer (ICT) from donor to acceptor moieties.…”
Section: Introductionmentioning
confidence: 99%